2017
DOI: 10.1007/s00262-017-2072-1
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-infiltrating immune cells as potential biomarkers predicting response to treatment and survival in patients with metastatic melanoma receiving ipilimumab therapy

Abstract: Monoclonal antibodies targeting immune checkpoints are gaining ground in the treatment of melanoma and other cancers, and considerable effort is made to identify biomarkers predicting the efficacy of these therapies. Our retrospective study was performed on surgical tissue samples (52 lymph nodes and 34 cutaneous/subcutaneous metastases) from 30 patients with metastatic melanoma treated with ipilimumab. Using a panel of 11 antibodies against different immune cell types, intratumoral immune cell densities were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
50
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 32 publications
7
50
1
1
Order By: Relevance
“…Balatoni et al showed that the strongest predictor of ipilimumab treatment response was the density of FOXP3+ cells infiltrating lymph node metastases; moreover Di Gennaro et al reported that electrochemotherapy induces a local response in skin melanoma metastasis by a lymphoid infiltrate characterised by a decrease in CD4+FOXP3+Treg cells. [27][28][29] Similarly, we demonstrated a different count of PD1+ out of the total CD4+ count in the control group (without regression) compared to the regressed group. The PD1/PDL1 axis maintains a balance between tolerance and autoimmunity, thus cancer cells under selective pressure can exploit this signalling pathway with lymphocytes to decrease the immune response.…”
Section: Discussionsupporting
confidence: 61%
“…Balatoni et al showed that the strongest predictor of ipilimumab treatment response was the density of FOXP3+ cells infiltrating lymph node metastases; moreover Di Gennaro et al reported that electrochemotherapy induces a local response in skin melanoma metastasis by a lymphoid infiltrate characterised by a decrease in CD4+FOXP3+Treg cells. [27][28][29] Similarly, we demonstrated a different count of PD1+ out of the total CD4+ count in the control group (without regression) compared to the regressed group. The PD1/PDL1 axis maintains a balance between tolerance and autoimmunity, thus cancer cells under selective pressure can exploit this signalling pathway with lymphocytes to decrease the immune response.…”
Section: Discussionsupporting
confidence: 61%
“…29 Several studies have found a close association between FOXP3 expression and the prognosis of patients in various tumors. 30,31 However, the controversial 34,43 while others have shown that FOXP3+ cells are a poor prognosis factor. 35,36 Therefore, 9 studies were included in our meta-analysis for the prognostic value of FOXP3+ TILs and demonstrated that FOXP3 TIL infiltration is a beneficial prognosis factor in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we also paid attention to the definition of time-to-event variables. In a few studies which mentioned the specific treatment, 28,43,58,59 OS was defined as the time from the date of start of the treatment to death or last follow-up, DFS was defined as the time from the date of start of the treatment to the date of first recurrence and/or disease progression (regional or distant metastases) or last follow-up, RFS was defined as the time from the date of start of the treatment to the date of the clinical recurrence. In two studies involved in Sentinel lymph node biopsy (SLNB), 16,52 RFS and OS were calculated from SLNB to an event (either recurrence or death) or until last follow-up.…”
Section: Study Selection and Basic Characteristicsmentioning
confidence: 99%
“…Major challenges to extending the efficacy of immunotherapy to more cancer patients include sustaining T cell activation and achieving T cell infiltration in the immunosuppressive microenvironment of solid tumors (Balatoni et al, 2018;Brown and Mackall, 2019;Cogdill et al, 2017;Darvin et al, 2018;Gajewski et al, 2013;Galon et al, 2006;Galon et al, 2012;Hamid et al, 2011;Mlecnik et al, 2011;Pages et al, 2005). Improved understanding of mechanisms controlling T cell differentiation and function is critical to overcoming these barriers.…”
Section: Introductionmentioning
confidence: 99%